PENGARUH MODEL PEMBELAJARAN SSCS TERHADAP HASIL BELAJAR SISWA KELAS VIII DI SMP NEGERI 2 KOTA KUPANG PADA MATERI SISTEM PEREDARAN DARAH - Adu, Debbi A.; Tokan, Moses K.; Yusnaeni, Yusnaeni (SINERGI : Jurnal Riset Ilmiah, 2026)
This study aims to determine the improvement in student learning outcomes through the influence of the SSCS learning model on the circulatory system in eighth-grade students at SMP Negeri 2 Kupang City in the 2025/2026 academic year. This study was a quasi-experimental study with a pretest-posttest control group design. Two sample classes were used: the experimental class using the SSCS learning model and the control class using the conventional learning model. Random sampling was used for sampling. The assessment instrument consisted of 10 multiple-choice questions and 5 essay questions. Learning outcome data, in the form of pretest-posttest results from both classes, were analyzed quantitatively using t-tests, preceded by prerequisite tests for normality and homogeneity. Based on the results of the treatment of the two classes, the normality values ​​of the pretest-posttest of the experimental class were obtained (0.063 > 0.05) and (0.100 > 0.05) while in the homogeneity test on the pretest of the control-experimental class (0.803 > 0.05) and posttest of the control-experimental class (0.172 > 0.05) so that the data were normally distributed and homogeneous, and the average posttest learning outcomes in the control class were 64.53 in the very low category while the average posttest results in the experimental class were 73.09 in the medium category, and supported by the results of the t-test with the results that there was an influence of the SSCS learning model on the Learning Outcomes of Class VIII students at SMP Negeri 2 Kupang City on the Circulatory System Material. This shows that the influence of the SSCS learning model can influence student learning outcomes to increase in class VIII of SMP Negeri 2 Kupang City.